Violência contra a mulher : uma fórmula discursiva - Panhan, Aline Salles (2021)
This reseach analyzes the occurrences of the syntagma “violência contra a mulher” (“violence against woman”) and its variations in the Brazilian discursive universe in the period from 2006 to 2021. The theoretical basis comes from Discourse Analysis (DA), specifically the notion of discursive formula proposed by Krieg-Planque (2010, 2018). Initially, the formulaic status of the syntagma “violência contra a mulher” is analyzed based on the four constitutive features of the formula described by Krieg-Planque (2010): i) to be a social referent, ii) to have a discursive dimension, iii) to have a crystallized character, iv) to be object of polemic. Assumed as a formula, “violência contra a mulher” shows itself as an expression that gathers in its surroundings a wide range of texts (the corpus is composed of different genres: news stories, cartoons, advertising campaigns, guidelines, videos, books, scientific articles etc.) that traverse the religious, academic/scientific, journalistic, judicial fields, among others, demonstrating its formulaic status. Then, a thorough investigation of the polemical aspect of the referred formula is conducted, underlining, particularly, the confrontation between public versus private and the image of the battered woman which emerges from the texts of the corpus. Thus, the analyses indicate that the formula is transitioning from a domestic matter that should be dealt with by the couple to a State issue. Furthermore, the corpus enabled us to analyze the different kinds of imagery of the battered woman that emerge from the texts. The analyses demonstrate that it is possible to make a connection between texts that organize data on violence against woman statistically (namely institutions such as the police, the criminal justice system, the NGOs...) and data released by the press: while in the former we find the profile of a victim as the woman generally depicted as poor, peripheral and black, in the latter we find cases of white, upper class and educated women. The main conclusion is that the public sphere considers violence perpetrated by man against woman as a crime that has to be reported; however, in the private sphere, violence against woman should be treated as a private matter. In addition to these, society holds the battered woman accountable for the violence she suffers, by claiming that she either deserved or chose violence. Thus, the perpetrator is pled “not guilty“. The imagery of the victim of violence is built based on “profiles“ spread by the police and the media, which, in turn, reinforces the stereotype of the poor and peripheral woman. However, domestic violence permeates all social classes.